2022
DOI: 10.3390/w14152391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus Fertilizer Application Rates on Colloidal Phosphorus Leaching in Purple Soil in Southwest China

Abstract: Phosphorus (P) lost via leaching from agricultural land is of major concern for water resource managers worldwide, and colloidal phosphorus (CP) may have a high contribution, since it is an important mobile form of P in soil and subsurface drainage. The objective of this study is to relate P fertilization application rates to CP leaching. To eliminate the influence of climate and facilitate the accurate measurement of P contents in different soil layers, we established soil columns to investigate the impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…A comparison of the average contents of TN, NO 3 − -N and TP in the 5 slopes of shallow groundwater revealed that the TN and NO 3 − -N concentrations were more significantly affected by the land utilization mode of the infiltration slopes, but their effect on the TP concentration was not obvious. This is mainly due to the reaction of phosphorus with the soil to form soil minerals, coupled with the adsorption and fixation of phosphorus in different soil layers, which limits its ability to migrate downwards in the soil (Zhang T et al, 2015;He et al, 2022). However, owing to the negative charge of the soil particles, the nitrogen fertilizer applied to the soil had a strong adsorption capacity for ammonium ions and a weak adsorption capacity for nitrate ions (Cai et al, 2016); additionally, the nitrogen Comparison of the average nitrogen and phosphorus contents and dispersion coefficients of shallow groundwater on different slopes.…”
Section: Analysis Of the Impact Of Slope Land Use Practices On Shallo...mentioning
confidence: 99%
“…A comparison of the average contents of TN, NO 3 − -N and TP in the 5 slopes of shallow groundwater revealed that the TN and NO 3 − -N concentrations were more significantly affected by the land utilization mode of the infiltration slopes, but their effect on the TP concentration was not obvious. This is mainly due to the reaction of phosphorus with the soil to form soil minerals, coupled with the adsorption and fixation of phosphorus in different soil layers, which limits its ability to migrate downwards in the soil (Zhang T et al, 2015;He et al, 2022). However, owing to the negative charge of the soil particles, the nitrogen fertilizer applied to the soil had a strong adsorption capacity for ammonium ions and a weak adsorption capacity for nitrate ions (Cai et al, 2016); additionally, the nitrogen Comparison of the average nitrogen and phosphorus contents and dispersion coefficients of shallow groundwater on different slopes.…”
Section: Analysis Of the Impact Of Slope Land Use Practices On Shallo...mentioning
confidence: 99%